Legal Education through MOOCs: A Study of Select International Online Platforms - Bakhshi, Samar Iqbal; Amees, Mohammad (Indian Journal of Educational Technology, 2022)
The study is inspired by the fact that Massive Open Online Courses (MOOCs) have penetrated the world’s higher education system to a great extent and emerged as a sustainable solution in the era of technology, especially during the COVID-19 pandemic; it has gained a broader impetus. The study is carried out by analyzing the actual data available on five major MOOC platforms at the international level; i.e. edX, Coursera, Udemy, LinkedIn Learning, and SWAYAM; offering courses in the subject ‘Law.’ The f indings reveal that the majority of the courses are offered from the Udemy platform. Most of the courses are offered on a payment basis; however, a good number of courses are available either free, or payment is required for certification only. It is also found that most of the courses are offered in the English language as well as most courses are offered for less than or equal to 48 hours duration. The study will provide an overview of the already offered courses through five select MOOCs platforms and encourage and motivate the students and legal practitioners to enrol in a course in their desired area. It may also abet the policymakers and intelligentsia, leveraging the potential of MOOCs to increase the quality of legal education as it exhibits an overall picture of the current scenario of its penetration into the higher education system. The study has excellent usability for stakeholders engaged in legal education and MOOCs research.